All Your Database Are Belong to Us. - MEIJER, ERIK (Communications of the ACM, 2012)
The article discusses the development of object databases in light of the rise of cloud computing, with particular emphasis on data availability and abstraction. A comparison is made between the perspectives of database development modelers and application programmers on issues related to data. Other topics include object-oriented programming, system collections services, and concurrency and threading in cloud computing. Computer programming languages addressed in the article include Structured Query Language (SQL), Java, and C++.